2003
DOI: 10.1097/00000542-200303000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Apoptosis-inducing Activity of Codeine and Codeinone

Abstract: Codeinone was found to possess both apoptosis and necrosis-inducing activity, in addition to the reported antinociceptive activity, further substantiating its antitumor potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Regarding the life threatening effects of morphine, they are generally expected to happen at high doses; in the present study we applied the maximum tolerance dose of opium (150 mg/kg). Although there are a large number of reports regarding the effects of opiate derivatives on cells apoptosis in the literature (7-9, 14, 19, 23), to our knowledge, this is the first study on the effects of opium on ovary cell apoptosis. In a previous study, we demonstrated that opium treatment can differentially induce brain and liver cell apoptosis in diabetic and non-diabetic male and female rats (6).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Regarding the life threatening effects of morphine, they are generally expected to happen at high doses; in the present study we applied the maximum tolerance dose of opium (150 mg/kg). Although there are a large number of reports regarding the effects of opiate derivatives on cells apoptosis in the literature (7-9, 14, 19, 23), to our knowledge, this is the first study on the effects of opium on ovary cell apoptosis. In a previous study, we demonstrated that opium treatment can differentially induce brain and liver cell apoptosis in diabetic and non-diabetic male and female rats (6).…”
Section: Discussionmentioning
confidence: 96%
“…Consumption of opium can effect some biochemical factors (3, 4), transforming growth factor β (TGF-β) (5), and causes brain and liver cells’ apoptosis (6). Considerable evidence is available suggesting that morphine (7-9), noscapine (10-13), codeine (14) and papaverine (15) have apoptotic activity in vitro and in vivo . Thus, the effect of opium on apoptosis and cell function could be different from pure drugs such as morphine, noscapine, codeine and papaverine because more than 20 alkaloids (16) and more than 70 constituents (17), have been detected in opium.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the growth inhibitory effects of codeine were increased by Fe(III), suggesting that the combination of morphine and Nx might be useful to supplement cancer therapy. We have recently found that codeinone had high cytotoxic activity against various cancer cell lines [28,29], as compared with codeine, suggesting its applicability for the treatment of cancer.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Apoptosis is also a pathologic feature of the brain injury, certain inflammatory diseases of the brain and central nervous system infection, such as human immunodeficiency virus (HIV)-associated dementia [2]. Apoptotic effects of opioids such as morphine [3-7], heroines [8], codeine [9], in neurons has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of literature on the effects of opium we aimed this project to examine its effects on brain and liver cells apoptosis. Apoptotic activity of morphine [3-5] noscapine [14-17], codeine [9] and papaverine [18] has been shown in the in vitro and in vivo experimental systems. Morphine promotes Jurkat cells apoptosis [3] Morphine enhances the expression of both Fas and Fas ligand (FasL), and induces macrophage apoptosis [6].…”
Section: Introductionmentioning
confidence: 99%